Mistrzyni Anna – Mistrzyni, która nie wie, że jest moim Mistrzem - Cywiński, Aleksander (Rocznik Pedagogiczny, 2019)
In the article, I present the pedagogy of the poet Anna Świrszczyńska. In particular, I refer to her drama Saint and Devil. Through this drama I show the consequences of using black pedagogy.